Choice, Interrupted: Travel and Inequality of Access to Abortion Services since the 1960s - Sethna, Christabelle; Palmer, Beth; Ackerman, Katrina; Janovicek, Nancy (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2013)
Travel is one of many extra-legal barriers that restrict access to abortion services. Paradoxically, women travel at the international, domestic, and local levels to circumvent legal and/or extra-legal barriers to access. Through an examination of four specific Canadian responses to inequality of access to abortion services relative to shifts in the legal terrain from the 1960s onwards, the authors demonstrate that travel signifies an interruption to reproductive choice. Women went to Britain and the United States for an abortion when these countries relaxed their abortion legislation. Within Canada, women sought out the services oﬀered by the Morgentaler Clinic in Montreal in order to avoid the abortion bureaucracy that limited their right to choose. In New Brunswick, the pro-life movement successfully lobbied hospitals to restrict abortion services, and the provincial government to deny funding for abortions performed in freestanding clinics, forcing women to travel to access abortion services. Pro-choice activists in southeastern British Columbia launched a successful campaign to protect hospital abortions, ensuring that rural women had access to abortion services within their home communities. Today, 25 years after the Supreme Court of Canada struck down the abortion law, abortion services are uneven at best and unattainable at worst in diﬀerent regions of the country.